2014
DOI: 10.1037/a0034337
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the longitudinal stability of the CSQ24 in a back pain population.

Abstract: These results provide support for the 4-factor structure of the CSQ24 and its longitudinal stability. Argument is provided for the need to explore the longitudinal stability of related tools in populations that undergo change as a result of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…However, LSE had a better therapeutic outlook than GAE because patient catastrophizing was significantly reduced only after 10 weeks of LSE. Harland and Martins reported that variability in catastrophizing scores over time is one of the factors suggesting effective treatment [47]. Also, this deduction of a more beneficial effect of LSE than GAE is buttressed by the result of this present study that the patient's ability to catastrophize was significantly lower in LSE compared to GAE.…”
Section: Discussionsupporting
confidence: 46%
“…However, LSE had a better therapeutic outlook than GAE because patient catastrophizing was significantly reduced only after 10 weeks of LSE. Harland and Martins reported that variability in catastrophizing scores over time is one of the factors suggesting effective treatment [47]. Also, this deduction of a more beneficial effect of LSE than GAE is buttressed by the result of this present study that the patient's ability to catastrophize was significantly lower in LSE compared to GAE.…”
Section: Discussionsupporting
confidence: 46%
“…When the nature of Cognitive Coping and Catastrophising is examined from a change perspective, Cognitive Coping has been shown to be resistant to change over a period of effective treatment, whereas Catastrophising has been shown to be variable in nature over time [ 23 ]. Taking these factors into account with Cognitive Coping apparently difficult to change with treatment and stable over time, therefore defining the patient more reliably than Catastrophising from a screening perspective, it is suggested that only Cognitive Coping is used to categorise patients into a high risk group.…”
Section: Discussionmentioning
confidence: 99%
“…The CSQ24 consists of 23 items about coping, with a 7-point Likert scale anchored with “Never Do That” and “Always Do That,” and one item measuring perceived control over pain with a 7-point Likert scale is anchored with “No Control” and “Complete Control.” The CSQ24 has four subscales: Catastrophising, Diverting Attention, Reinterpreting, and Cognitive Coping; each subscale is scored from 0 to 36. The CSQ24 has demonstrated a good level of validity as a measure of coping in individuals with CLBP [ 19 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations